Near Point of Convergence After a Sport-Related Concussion: Measurement Reliability and Relationship to Neurocognitive Impairment and Symptoms. (December 2015) - Pearce, Kelly L.; Sufrinko, Alicia; Lau, Brian C.; Henry, Luke; Collins, Michael W.; Kontos, Anthony P.
Background: Convergence insufficiency (CI) is a common binocular vision deficit after a sport-related concussion (SRC). CI may result in visual discomfort and vision-mediated functional difficulties such as slowed reading and compromised attention, leading to impaired academic, work, and sport performance. Purpose: To test the reliability of repeated near point of convergence (NPC) measurements in a sample of athletes after an SRC; compare the symptoms and cognitive impairment of athletes with normal NPC to those with CI after an SRC; and explore the relationship among age, sex, learning disability, migraine history, and CI. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 78 athletes (mean age, 14.31 ± 2.77 years) who were seen a mean 5.79 ± 5.63 days after an SRC were administered 3 trials of an NPC assessment, along with neurocognitive (Immediate Post-Concussion Assessment and Cognitive Testing [ImPACT]) and symptom assessments. Patients were divided into normal NPC (NPC ≤5 cm; n = 45) and CI (NPC >5 cm; n = 33) groups. Intraclass correlation coefficients (ICCs) and repeated-measures analyses of variance (ANOVAs) assessed the consistency of NPC across the 3 trials. The ANOVAs were employed to examine differences on neurocognitive composites and symptoms between the normal NPC and CI groups. Stepwise regressions (controlling for age and symptom scores on the Post-Concussion Symptom Scale [PCSS]) were conducted to evaluate the predictive utility of the NPC distance for neurocognitive impairment. Results: Groups did not differ on demographic or injury characteristics. NPC differed between trial 1 and trials 2 ( P = .02) and 3 ( P = .01) for the CI group but not the normal NPC group. Internal consistency was high across NPC measurements (ICC range, 0.95-0.98). Patients with CI performed worse on verbal memory ( P = .02), visual motor speed ( P = .02), and reaction time ( P = .001, η 2 = .13) and had greater total symptom scores ( P = .02) after the injury. Results of hierarchical regression revealed that the NPC distance contributed significantly to the model for reaction time ( P < .001). Conclusion: CI was common ( 42%) in athletes evaluated within 1 month after an SRC. Athletes with CI had worse neurocognitive impairment and higher symptom scores than did those with normal NPC. Clinicians should consider routinely screening for NPC as part of a comprehensive concussion evaluation to help inform treatment recommendations, academic accommodations, and referrals for vision therapy.